Dimensionamiento de un reactor para la producción del detergente líquido autopolish a nivel industrial en la empresa Produqum LTDA. (2017)
The present work has the purpose of the design of a reactor for the manufacturing process of the Autopolish detergent in Produquim Ltda. For the development of the project the current process was diagnosed, establishing the procedures performed, their deficiencies and critical variables such as pH, temperature, Density, viscosity and alkalinity. In this way, it was identified that the parameters should be evaluated in a quantitative way to ensure the quality of the product. Subsequently, an experimental phase was carried out to define the physical and chemical characteristics of the product and the specifications were established in each of the mentioned parameters.